Does automatic funding suck? The cost and value of automatic funding in small nation screen industries in Northern Europe. Issue 3 (16th April 2021) - Sørensen, Inge Ejbye; Redvall, Eva Novrup
ABSTRACT: Recent years have seen a rise in automatic funding schemes in the screen industries. This article examines the intended and unintended consequences of automatic incentives in smaller screen economies in Northern Europe. It focuses on the Danish Film Institute's decision to abolish automatic schemes including tax incentives, and compares this case to other screen industries where automatic funding is well established or has been recently introduced. Based on discussions with executives and funders at national screen agencies, the article investigates who benefits from specific funding schemes and which screen industry automatic incentives prioritise and facilitate. Through this, it examines the political considerations and value systems that underpin funding priorities, and the perception of automatic funding among policy makers, implementers and stakeholders in national screen industries. The analysis indicates that automatic funding is rarely a proactive measure, but rather a response to failing screen industries or competition from neighbouring funding incentives.